2019
DOI: 10.1186/s12864-018-5410-6
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA expression profile of HCT-8 cells in the early phase of Cryptosporidium parvum infection

Abstract: BackgroundCryptosporidium parvum is an important zoonotic parasitic disease worldwide, but the molecular mechanisms of the host–parasite interaction are not fully understood. Noncoding microRNAs (miRNAs) are considered key regulators of parasitic diseases. Therefore, we used microarray, qPCR, and bioinformatic analyses to investigate the intestinal epithelial miRNA expression profile after Cryptosporidium parvum infection.ResultsTwenty miRNAs were differentially expressed after infection (four upregulated and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 44 publications
3
18
1
Order By: Relevance
“…Our previous study found that miR-942-5p was strongly upregulated in HCT-8 cells following C. parvum infection, compared with uninfected cells [18]. In this study, qPCR assays revealed that the transcription of the miR-942 gene was significantly decreased after blocking either TLR2 or TLR4 (F (2, 23) = 58.32, P = 10 −9 by one-way ANOVA: test versus control group for Fig.…”
Section: Both Tlr2 and Tlr4 Contribute To Upregulation Of Mir-942-5pmentioning
confidence: 48%
See 2 more Smart Citations
“…Our previous study found that miR-942-5p was strongly upregulated in HCT-8 cells following C. parvum infection, compared with uninfected cells [18]. In this study, qPCR assays revealed that the transcription of the miR-942 gene was significantly decreased after blocking either TLR2 or TLR4 (F (2, 23) = 58.32, P = 10 −9 by one-way ANOVA: test versus control group for Fig.…”
Section: Both Tlr2 and Tlr4 Contribute To Upregulation Of Mir-942-5pmentioning
confidence: 48%
“…As previously described, oocysts were excysted in 0.25% trypsin and 0.75% sodium taurocholate for 1 h with mixing every 5 min, followed by incubation at room temperature for 30 min [19,20]. HCT-8 human ileocecal adenocarcinoma cells (American Type Culture Collection, Manassas, VA) were maintained in Dulbecco's modified Eagle's medium (DMEM) supplemented with 10% fetal bovine serum, 4 mmol/l l-glutamine, 100 U/ml penicillin, and 100 U/ml streptomycin at 37 °C in a humidified 5% CO 2 incubator [18]. Cell monolayers in 24-well cell culture dishes were inoculated with 2.5 × 10 6 purified sporozoites per well in DMEM.…”
Section: Cryptosporidium Oocysts and Hct-8 Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, C. parvum infection downregulates the expression of miR-98 and let-7 family to induce the suppressor of cytokine signaling (SOCS4) proteins that are negative regulators of cytokine signaling (Hu et al 2010 ; Sato et al 2017 ). Recently, Wang and collaborators ( 2019 ) reported for the first time the miRNA expression profile of human intestinal epithelial cells infected with C. parvum and they evidenced that most miRNAs were not significantly differentially expressed in the infected HCT-8 cells as compared to uninfected cells. Nonetheless, they reported that the miR-34b-5p, miR-18b-3p, miR-3976, and miR-3591-3p were downregulated after C. parvum infection and those have been associated with the regulation of both apoptotic processes and epithelial immune responses, targeting genes, such as ELAVL1, RAB10, RAB14, ELK4, SOS2, TAB2, DAXX, fibroblast growth factor 14 (FGF14), and MAPK3.…”
Section: Mirnas: Fine Modulators Of Parasitic Infectionsmentioning
confidence: 99%
“…Additionally, the application of epidermal growth factor (EGF) to the cell culture resulted in the inhibition of apoptotic processes induced by Cryptosporidium [68]. Furthermore, it was found that the process is extremely complex and determined by numerous factors, among others, by the research model, duration of infection, and the developmental stage of the parasite [69][70][71][72][73][74][75][76][77].…”
Section: Cryptosporidium Spmentioning
confidence: 99%